2016
DOI: 10.1016/j.clinph.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cerebellar theta-burst stimulation on arm and neck movement kinematics in patients with focal dystonia

Abstract: Objective To investigate the cerebellar inhibitory influence on the primary motor cortex in patients with focal dystonia using a cerebellar continuous theta-burst stimulation protocol (cTBS) and to evaluate any relationship with movement abnormalities. Methods Thirteen patients with focal hand dystonia, 13 patients with cervical dystonia and 13 healthy subjects underwent two sessions: (i) cTBS over the cerebellar hemisphere (real cTBS) and (ii) cTBS over the neck muscles (sham cTBS). The effects of cerebella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 55 publications
2
50
1
Order By: Relevance
“…Several studies have found normal cerebellar function or connectivity in idiopathic cervical dystonia patients, or abnormal cerebellar function only in cervical dystonia patients with tremor (Delnooz et al, 2013;Sadnicka et al, 2014;Antelmi et al, 2016;Bologna et al, 2016;Avanzino et al, 2018). Here, we found that all lesions causing cervical dystonia were connected to the cerebellum, including cases with no head tremor ( Supplementary Fig.…”
Section: The Cerebellum In Cervical Dystoniasupporting
confidence: 60%
“…Several studies have found normal cerebellar function or connectivity in idiopathic cervical dystonia patients, or abnormal cerebellar function only in cervical dystonia patients with tremor (Delnooz et al, 2013;Sadnicka et al, 2014;Antelmi et al, 2016;Bologna et al, 2016;Avanzino et al, 2018). Here, we found that all lesions causing cervical dystonia were connected to the cerebellum, including cases with no head tremor ( Supplementary Fig.…”
Section: The Cerebellum In Cervical Dystoniasupporting
confidence: 60%
“…torticollis / laterocollis / anterocollis / retrocollis) and simple voluntary head rotation of the healthy controls, the direction and extent of the cerebellar priming of PAS effects were similar. This is in contrast with recordings in writer’s cramp patients, in whom both types of cerebellar stimulation did not influence PAS effects 13 , 33 .…”
Section: Discussioncontrasting
confidence: 99%
“…In this respect, it is interesting to note that modulation of cerebellar cortex excitability, by means of cTBS and iTBS, seems to have a different effect on M1 excitability in patients with focal hand dystonia and cervical dystonia. Cerebellar cTBS can reduce M1 excitability, measured by I/O curves, in patients with cervical dystonia but not in those with focal hand dystonia (Table ) . Similarly, in cervical dystonia, cerebellar inhibition suppressed the effect of PAS while cerebellar excitation enhanced it, whereas in writer's cramp, cTBS/iTBS of the cerebellum had no effect on PAS‐induced plasticity .…”
Section: Methodsmentioning
confidence: 99%
“…Cerebellar cTBS can reduce M1 excitability, measured by I/O curves, in patients with cervical dystonia but not in those with focal hand dystonia (Table 3). 124 Similarly, in cervical dystonia, cerebellar inhibition suppressed the effect of PAS while cerebellar excitation enhanced it, 125 whereas in writer's cramp, cTBS/iTBS of the cerebellum had no effect on PASinduced plasticity. 126 Interestingly, the effect was different between PAS responders and non-responders.…”
Section: Variability In Motor Cortical Plasticitymentioning
confidence: 99%